Is antibiotic prophylaxis necessary after endoscopic ultrasound–guided fine-needle aspiration of pancreatic cysts? - Seifeldin Hakim; Mihajlo Gjeorgjievski; Zubair Khan; Michael E. Cannon; Kevin Yu; Prithvi Patil; Roy Tomas DaVee; Sushovan Guha; Ricardo Badillo; Laith Jamil; Nirav Thosani; Srinivas Ramireddy (Clinical Endoscopy, 2022)
Background/Aims: Current society guidelines recommend antibiotic prophylaxis for 3 to 5 days after endoscopic ultrasound–guided fine-needle aspiration (EUS-FNA) of pancreatic cystic lesions (PCLs). The overall quality of the evidence supporting this recommendation is low. In this study, we aimed to assess cyst infection and adverse event rates after EUS-FNA of PCLs among patients treated with or without postprocedural prophylactic antibiotics. Methods: We retrospectively reviewed all patients who underwent EUS-FNA of PCLs between 2015 and 2019 at two large-volume academic medical centers with different practice patterns of postprocedural antibiotic prophylaxis. Data on patient demographics, cyst characteristics, fine-needle aspiration technique, periprocedural and postprocedural antibiotic prophylaxis, and adverse events were retrospectively extracted. Results: A total of 470 EUS-FNA procedures were performed by experienced endosonographers for the evaluation of PCLs in 448 patients, 58.7% of whom were women. The mean age was 66.3±12.8 years. The mean cyst size was 25.7±16.9 mm. Postprocedural antibiotics were administered in 274 cases (POSTAB+ group, 58.3%) but not in 196 cases (POSTAB– group, 41.7%). None of the patients in either group developed systemic or localized infection within the 30-day follow-up period. Procedure-related adverse events included mild abdominal pain (8 patients), intra-abdominal hematoma (1 patient), mild pancreatitis (1 patient), and perforation (1 patient). One additional case of pancreatitis was recorded; however, the patient also underwent endoscopic retrograde cholangiopancreatography. Conclusions: The incidence of infection after EUS-FNA of PCLs is negligible. Routine use of postprocedural antibiotics does not add a significant benefit.